Online information system for the Department of Tourism in Southern Mindanao - Masacupan, Maepril Louise Tingson (2009)
The Department of Tourism in Southern Mindanao, like any other government sector in the Philippines has a task of promoting the country?s natural and man-made resources to individuals who wish to visit the country. Challenges are faced in promoting Southern Mindanao, and especially disseminating information regarding it. This Online Information System for the Department of Tourism in Southern Mindanao (OISDOT ?XI) enables tourists to have a glimpse of what the region has to offer with just a click of the mouse anytime and anywhere. The user can choose from the four major provinces of the region to trim down the searching process. The information system lists all destination places and tourism establishments available. The search result also provides the name, location, contact information, the rates, accommodation and services offered. It also offers tourism information like news and events, the tourism calendar, graphical information and, updates regarding the entire region. The data in the system is maintained and organized by an administrator. The administrator is responsible of deleting and adding information to the system?s database as well as uploading of photos and maps. The system is equipped with hyperlink maps and pictures to provide a user friendly database. Moreover, the IOSTDOT-XI provides a forum which is a convenient way of exchanging information between tourists and DOT personnel